Investigating the Effect of Training Career Path Skills based on Super’s Career Development Theory on Academic Self-Concept of Students of Isfahan University - Pasha, Shima (2020)
The present study aimed to investigate the effect of training career path skills based on Super’s Development Theory on students’ academic self-concept. The study is a quasi-experimental with pretest-posttest design with a control group. The statistical population of the study consisted of all students of University of Isfahan year 2018. Using available sampling method, 30 people were selected and randomly, 15 of them were placed in the test group and 15 in the control group. The data collection tool was Academic Self-Concept Scale (ASCS) (Reynolds et al, 1980). The career path skills were trained to the test group for ten 90-minute sessions in groups, and no training was provided to the test group. The data were analyzed using SPSS software at the level of descriptive statistics including mean and standard deviation and at the level of inferential statistics by covariance analysis method. The results showed that training career path skills based on Super’s Development Theory has a significant positive effect on students’ academic self-concept.